Integration of Ecological Spirituality and Youth Participation in Reforestation Program: Laudato Si’ Movement Timor Leste - Josue Willian; Abdul Jabbar; Andhina Putri Heriyanti (Yayasan Ekologi Masyarakat dan Sains, 2026)
Deforestation in Timor-Leste persists at 10,000–12,000 hectares annually, yet reforestation research remains theoretically fragmented, emphasizing biophysical dimensions while neglecting the spiritual and attitudinal values that drive youth participatory environmental behavior. This study examines how ecological spirituality, operationalized through Laudato Si's three dimensions (spiritual, lifestyle, and societal), shapes environmental attitudes, mediates youth participation in reforestation, and produces ecological and social outcomes. Using a mixed-method light approach, 23 purposively selected informants participated in in-depth interviews and thematic analysis, complemented by land suitability assessments and plant survival measurements at two reforestation sites in Díli, Timor-Leste. Findings reveal that Laudato Si's three dimensions function as interconnected psychological mechanisms that progressively transform individual moral awareness into collective environmental action. Despite strong spiritual motivation, youth participation remained predominantly consultative (Arnstein's tokenism level) due to centralized decision-making and limited resource autonomy. Field assessments classified both sites as marginally suitable (S3), with plant survival rates of 50–80%; drought-tolerant neem (Azadirachta indica) achieved the highest survival rate (80%). This study introduces the ESYPESO Framework as a novel integrated analytical model empirically mapping causal pathways among ecological spirituality, environmental attitudes, participatory behavior, and ecological and social outcomes within a youth-led movement.